Erratum: ``The Beaming Pattern and Spectrum of Radiation from Inverse Compton Scattering in Blazars'' (ApJ, 561, 111 [2001]) - Georganopoulos, M.; Kirk, J. G.; Mastichiadis, A. (The Astrophysical Journal, 2004)
Equation (5) in § 2 should readf(x)=[2xlnx+x+1-2x2+(4∊0γx)22(1+4∊0γx)(1-x)]P(1/4γ2,1,x),x=∊4∊0γ2(1-∊/γ),(5)as given by F. C. Jones (ApJ, 561, 111 [2001]). In our original paper, the factor (1-x) in the final term inside the bracket was missing. The correct form was used in all computations.
Keywords: addenda; errata